A Longitudinal Analysis of Variation in Psychological Well-being and Body Image in Patients Before and After Bariatric Surgery. Issue 5 (May 2020) - deMeireles, Alirio J.; Carlin, Arthur M.; Bonham, Aaron J.; Cassidy, Ruth; Ross, Rachel; Stricklen, Amanda; Finks, Jonathan; Ghaferi, Amir A.
Abstract : Supplemental Digital Content is available in the text